2023
DOI: 10.3390/bios13110977
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanoparticle-Enhanced Optical Techniques for Cancer Biomarker Sensing

Li Fu,
Cheng-Te Lin,
Hassan Karimi-Maleh
et al.

Abstract: This review summarizes recent advances in leveraging localized surface plasmon resonance (LSPR) nanotechnology for sensitive cancer biomarker detection. LSPR arising from noble metal nanoparticles under light excitation enables the enhancement of various optical techniques, including surface-enhanced Raman spectroscopy (SERS), dark-field microscopy (DFM), photothermal imaging, and photoacoustic imaging. Nanoparticle engineering strategies are discussed to optimize LSPR for maximum signal amplification. SERS ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 214 publications
0
2
0
Order By: Relevance
“…In the last decades, AI and high-performance computing (HPC) have enabled more feasible computational costs . There have been several reports of DL implementation for biomolecular enantiomer sensing. Yang et al have reported a wearable plasmonic sensor based on flexible plasmonic metamaterials with surface-enhanced Raman scattering (SERS) . The sensor had a superlattice metafilm structure that is prone to deformations and thus can potentially alter SERS activity.…”
Section: Emerging Applications Of Ai-based Metamaterials Design In He...mentioning
confidence: 99%
“…In the last decades, AI and high-performance computing (HPC) have enabled more feasible computational costs . There have been several reports of DL implementation for biomolecular enantiomer sensing. Yang et al have reported a wearable plasmonic sensor based on flexible plasmonic metamaterials with surface-enhanced Raman scattering (SERS) . The sensor had a superlattice metafilm structure that is prone to deformations and thus can potentially alter SERS activity.…”
Section: Emerging Applications Of Ai-based Metamaterials Design In He...mentioning
confidence: 99%
“…In the field of optoelectronics, light–matter strong coupling can also be utilized to realize ultrafast light modulator components [ 9 ] and efficient photovoltaic materials [ 10 ]. In the meantime, in the field of biomedicine, light–matter strong coupling is also widely used in fluorescence imaging, photothermal therapy, and other aspects [ 11 ]. Therefore, the light–matter strong coupling holds great significance in the development of novel optical technologies along with the promotion of great scientific research.…”
Section: Introductionmentioning
confidence: 99%